Characteristics of social media 'detoxification' in university students. Issue 1 (1st January 2021) - El-Khoury, Joseph; Haidar, Riwa; Kanj, Rama Rand; Bou Ali, Linda; Majari, Ghaidaa
ABSTRACT: The multiplication of social networking sites has led to increased frequency of use among young adults. While the association with mental wellbeing is still controversial, high levels of social media use were correlated with problematic behaviours, low self-esteem and depressive symptoms. 'Social Media Detoxification' (Detox) is the term used to describe voluntary attempts at reducing or stopping social media use to improve wellbeing. We conducted a pilot study to explore the characteristics of social media detoxification applied by 68 university students in their social media activity. Descriptive analysis revealed that most students reported a positive change in mood, reduced anxiety and improved sleep during and in the immediate aftermath of the detoxification period. These preliminary findings show that 'social media detoxification' is a phenomenon understood and used by university students to moderate their social media use. Wide variability in its application and effects is noted in our sample.